DNA-like Helices as Nanosized Polarizers of Electromagnetic Waves - Semchenko, Igor V.; Mikhalka, Ivan S.; Khakhomov, Sergei A.; Samofalov, Andrey L.; Balmakou, Aliaksei P. (Frontiers in Nanotechnology, 2022)
The possibility of using a conducting double DNA-like helix as the basis of an electromagnetic wave polarizer, which converts an incident linearly polarized wave into a reflected wave with circular polarization, has been shown. A high-frequency resonance is investigated, at which the wavelength of the incident radiation is approximately equal to the length of a helix turn. The simulation of a double DNA-like helix has been carried out. The electric currents arising in the helical strands under waves with circular polarization at high-frequency resonance have been analyzed. Fundamentally different behavior of the double DNA-like helix concerning waves with right-hand or left-hand circular polarization has been established, which can be called the effect of polarization selectivity. This effect is manifested in the fact that a double DNA-like helix at high-frequency resonance can create a reflected wave having only one sign of circular polarization. The electric vector of the reflected wave produces a turn in space with the opposite winding direction compared to the double helix itself. These studies also highlight the electromagnetic forces of interaction between helical strands. The equilibrium of the double DNA-like helix has been studied, including as an element of metamaterials and as an object with a high potential for use in nanotechnology.